Barriers to establishing shared decision‐making in childbirth: Unveiling epistemic stereotypes about women in labour. Issue 2 (29th March 2020) - Villarmea, Stella; Kelly, Brenda
Abstract: Rationale, aims, and objectives: The benefits for shared decision‐making (SDM) in delivery of high‐quality and personalized care are undisputed, but what is it about the dynamics of the delivery room that leads some to doubt that true SDM is possible? How difficult can it be to establish SDM as the norm when caring for a woman in labour? The discussion around SDM, autonomy, and rationality is timely and highly relevant to wider practice. Method: The concept of a person's autonomy in decision‐making about their body and health is generally accepted and is indeed enshrined in law in many countries. This ought to lay the foundation for SDM in obstetrics. Yet, women's experience speaks to an uncomfortable truth, namely, that it is far from commonplace. We are interested in exploring this tension between the law and the practice. Results: We examine a theory of female rationality and its application to women in labour, and juxtapose this with the view from the front line of care delivery. Is a woman in labour able to fully engage in an SDM process? In answering this question, associations in the discourses and practises around women's capacity during labour are revealed, which act as barriers, consciously or unconsciously, to establishing SDM as the norm in obstetrics and midwifery. Conclusion(s): The recent UN report advocating a human rights‐based approach to end mistreatment and violence against women in reproductive health services has a particular focus on childbirth and obstetric violence. This paper contributes to the recognition of obstetric violence as a human rights violation. It offers conceptual tools to diagnose the impact of gender stereotypes during childbirth and to eliminate women's discrimination in the field of reproductive health.